BIOSSEGURANÇA COMO UMA ESTRATÉGIA DE PREVENÇÃO DO ESTRESSE - Freitas, Ana Kelly dos Santos (2019)
Introduction: Accidents with biological material during the workday can incur stress to the worker, impacting on his personal, professional and social life. In this way, biosafety can be an important strategy to prevent this stress, since it involves prev